MicroRNA‐34a Mediates the Aldosterone‐Induced Acceleration of Endothelial Senescence - Jia, Minyue; Lin, Liya; Yang, Boyun; Yu, Hanxiao; Zhong, Shan; Xu, Xiaohong; Song, Xiaoxiao (International journal of hypertension, 2025)
Inappropriate aldosterone production relative to sodium status is known to induce arterial hypertension and cause detrimental effects on endothelium and vascular remodeling. This study investigated whether microRNAs (miRs) serve as key mediators of aldosterone’s effects on endothelial dysfunction. Using human umbilical vein endothelial cells (HUVECs) as a model system, we demonstrated that aldosterone treatment suppressed cellular proliferation and migration while promoting senescence. Mechanistically, we observed that aldosterone exposure significantly upregulated miR‐34a expression in HUVECs. The functional significance of miR‐34a was confirmed when specific inhibitors reversed aldosterone’s antiproliferative and prosenescence effects. To elucidate the underlying molecular pathway, we performed comprehensive biological analyses, which revealed that miR‐34a target genes were predominantly associated with the Notch signaling pathway. Western blot analysis further validated that miR‐34a promotes senescence in HUVECs through negative regulation of NOTCH1. Collectively, our findings identify miR‐34a as a crucial mediator of aldosterone‐induced endothelial cell senescence via the NOTCH1 signaling pathway, suggesting its potential as a therapeutic target for aldosterone‐related vascular diseases.